2020
DOI: 10.1002/mds.28397
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Expanded Repeats by Small Molecules in Repeat Expansion Disorders

Abstract: Recent technological advancements in genetic analysis have allowed for the consecutive discovery and elucidation of repeat expansion disorders: diseases caused by the abnormal expansion of repeat sequences in the genome. Many of these repeat expansion disorders are neurodegenerative movement disorders. Radical cures for these disorders have yet to be established. Although conventional treatments for repeat expansion disorders have mainly targeted the abnormal mRNA and proteins encoded by the affected genes, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Previous studies have demonstrated the involvement of DNA repair proteins in repeat instability in repeat expansion disorders, such as DM1. 52 To examine whether the expression of these genes involved in DNA repair relates to the differences in repeat instability in each CNS cell lineage of DM1, we analyzed gene expression of mismatch repair genes ( MSH2 , MSH3 and MSH6 ) and FAN1 . There was no difference between the DM1 and control groups in each CNS cell lineage, but there was a trend toward a lower expression of these genes in the spinal cord than in the cortex and white matter ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated the involvement of DNA repair proteins in repeat instability in repeat expansion disorders, such as DM1. 52 To examine whether the expression of these genes involved in DNA repair relates to the differences in repeat instability in each CNS cell lineage of DM1, we analyzed gene expression of mismatch repair genes ( MSH2 , MSH3 and MSH6 ) and FAN1 . There was no difference between the DM1 and control groups in each CNS cell lineage, but there was a trend toward a lower expression of these genes in the spinal cord than in the cortex and white matter ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although a promising avenue, the issue of off-target effects of the ASOs and other Htt-knockdown approaches in humans is a concern. A recent report described the identification of a chemical that binds expanded CAG tracts and promotes contraction of the repeats, which could have value in the treatment of HD and other CAG-repeat expansion disorders [ 110 , 111 ].…”
Section: The Diseasesmentioning
confidence: 99%
“…Inefficient repair of tandem repeats often leads to repeat expansions or contractions. There are over one million tandem repeats in the human genome, many of which are polymorphic, and their expansion is causal for many disorders [ 16 , 209 , 210 ] such as Huntington disease, spinocerebellar ataxias, Friedreich ataxia and Fragile X syndrome [ 16 , 209 , 210 ]. There is growing evidence that persistent R-loop formation can result in genomic instability [ 211 ] and R-loops are implicated in a number of diseases including cancers, autoimmune and neurological disorders [ 15 , 43 , 212 ].…”
Section: Non-canonical Secondary Structures In Diseasementioning
confidence: 99%